An experimental study of shatkora (Citrus Macroptera) in a tray dryer: Effect on drying kinetics and product quality - Uddin, M. Rakib; Akter, Syeada Nelima; Pervez, Md. Shahria; Thurga Devi, Munusamy; Khan, Maksudur R. (Universiti Malaysia Pahang, 2019)
Citrus macroptera is a citrus fruit locally known as Shatkora and the fruit of this plant were used for various purposes especially for cooking and also as an odorant in perfume industries.In this research work, Shatkora peel was dried using a laboratory scale tray dryer. The experimental work was conducted at an inlet temperature of 40–60°C and velocities from 0.5–0.9 m/s. Besides, the thickness of the layer was varied between 2– 10 mm. The results demonstrated that the rate of drying was increased accordingly with rise in both air temperature and air velocity however a decreased in layer thickness was noticed. At high air temperature, moisture content of solid achieved equilibrium state within short period of time. On the other hand, moisture diffusivity of Shatkora was evaluated by applying Fick’s second law and the value was varied from 1.78 × 10-8 to 2.83 × 10-7. In addition, activation energy was determined by using Arrhenius type relation and 19.70 kJ/mol was obtained.